Application of low loading of collagen in electrospun poly[(L-lactide)-co-(ε-caprolactone)] nanofibrous scaffolds to promote cellular biocompatibility - Donraporn Daranarong (2018)
Blending poly[(L-lactide)-co-(ε-caprolactone)] with 2.0% (w/w) collagen significantly changes electrospun fibre morphology, which assists in improving the initial attachment and health of olfactory ensheathing cells. Electrospinning of various polymers has been used to produce nanofibrous scaffolds that mimic the extracellular matrix and support cell attachment for the potential repair and engineering of nerve tissue. In the study reported here, an electrospun copolymer of L-lactide and ε-caprolactone (67:33mol%) resulted in a nanofibrous scaffold with average fibre diameter and pore size of 476 ± 88 and 253 ± 17nm, respectively. Blending with low loadings of collagen (<2.5% w/w) significantly reduced the average diameter and pore size. The uniformity of fibre diameter distributions was supported with increasing collagen loadings. The nanofibrous scaffolds significantly promoted the attachment and proliferation of olfactory ensheathing cells compared to cells exhibiting asynchronous growth. Furthermore, analysis of cell health through mitochondrial activity, membrane leakage, cell cycle progression and apoptotic indices showed that the nanofibrous membranes promoted cell vigour, reducing necrosis. The study suggests that the use of more cost-effective, low loadings of collagen supports morphological changes in electrospun poly[(L-lactide)-co-(ε-caprolactone)] nanofibrous scaffolds, which also support attachment and proliferation of olfactory ensheathing cells while promoting cell health. The results here support further investigation of the electrospinning of these polymer blends as conduits for nerve repair. © 2013 Society of Chemical Industry.